Feasibility of a sutureless anastomotic technique in robot-assisted vascular surgery - Balazs C. Lengyel, MD; Charudatta S. Bavare, MD; Rebecca G. Swann, MT; Ponraj Chinnadurai, MBBS, MMST; Alan B. Lumsden, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
While other specialties embraced robotic technology, vascular surgery was revolutionized by endovascular techniques. The combination of open surgical techniques with endovascular solutions became standard practice; however, it is considered an unexplored frontier in the evolving field of robotic vascular procedures. One of the criticisms against robotics is the difficulty of vascular anastomosis. Hybrid grafts—although now discontinued—were once used for sutureless vascular anastomosis during open reconstructions. This article evaluates the feasibility of a sutureless anastomotic technique by reincarnating the idea of the hybrid vascular graft: a PTFE graft connected to a self-expanding covered stent.